2021
DOI: 10.1126/sciimmunol.abd5778
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of resident and circulating precursors to tumor-infiltrating CD8 + T cell populations in lung cancer

Abstract: Tumor-infiltrating lymphocytes (TILs), in general, and especially CD8+ TILs, represent a favorable prognostic factor in non–small cell lung cancer (NSCLC). The tissue origin, regenerative capacities, and differentiation pathways of TIL subpopulations remain poorly understood. Using a combination of single-cell RNA and T cell receptor (TCR) sequencing, we investigate the functional organization of TIL populations in primary NSCLC. We identify two CD8+ TIL subpopulations expressing memory-like gene modules: one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 50 publications
10
94
1
Order By: Relevance
“…Mapping the T Ldys signature onto this dataset suggested a close association of T cells with T Ldys with KLF2 and GZMK precursor clusters, whereas the exhaustion signature derived from CD8 + c1 T cells mapped to the exhausted LAYN cluster. Gueguen et al (53) found limited differentiation of KLF2 and GZMK precursor populations to exhausted LAYN T cells, consistent with our data that T cells with T Ldys failed to acquire effector and exhaustion molecules. Multiple studies found that exhausted CD8 + T cells correlate with good responses to ICB in patients with NSCLC (60)(61)(62), and the presence of a T cell-derived IFN- signature and PD-L1 up-regulation is predictive for ICB response in NSCLC.…”
Section: Discussionsupporting
confidence: 93%
“…Mapping the T Ldys signature onto this dataset suggested a close association of T cells with T Ldys with KLF2 and GZMK precursor clusters, whereas the exhaustion signature derived from CD8 + c1 T cells mapped to the exhausted LAYN cluster. Gueguen et al (53) found limited differentiation of KLF2 and GZMK precursor populations to exhausted LAYN T cells, consistent with our data that T cells with T Ldys failed to acquire effector and exhaustion molecules. Multiple studies found that exhausted CD8 + T cells correlate with good responses to ICB in patients with NSCLC (60)(61)(62), and the presence of a T cell-derived IFN- signature and PD-L1 up-regulation is predictive for ICB response in NSCLC.…”
Section: Discussionsupporting
confidence: 93%
“…Among CD8 T cell clusters, we observed that LNs were enriched for CD8-Naïve and CD8-TCF1 cells, while adjacent normal regions were enriched in CD8-EFF cells (Fig 2B). The two exhausted CD8 clusters were enriched in the tumor regions relative to adjacent normal regions, and this effect was more pronounced in the tumor bed regions with viable cancer cells, which is consistent with prior reports 12,15,16 . These exhausted CD8 clusters also demonstrated greater clonal expansion relative to the adjacent normal and tumor regions without viable cancer cells (Fig S5D).…”
Section: Treg Tfh and Exhausted Cd8 T Cells Are Enriched In Tumor Regions With Viable Cancer Cellssupporting
confidence: 91%
“…Considering the clonal expansion of TFH, Treg, and exhausted CD8 T cells in viable tumor regions, we hypothesized that tumor antigen-specific TCR-driven proliferation in the tumor microenvironment mediated this enrichment. Indeed, others have proposed that CD8 T cells undergo an additional burst of proliferation in the vicinity of viable tumor, potentially attributable to re-engagement of the TCR in the tumor microenvironment 16 . By identifying TCR clones present in both the tumor regions with and without viable cancer cells, we examined the proliferation of clone-matched T cells in the two regions.…”
Section: Clonal Expansion Of Tumor Regional T Cells Is Not Associated With Cancer Cell-induced Proliferationmentioning
confidence: 99%
“…TILs, especially CD8+ TILs, represent a favorable prognostic factor in several types of cancers (Gueguen et al 2021). Meanwhile, CD8+ TILs performed as the nal executor of PD1/PD-L1 pathway.…”
Section: Tumor-related Immune Heterogeneity Between Primary Lesions and Paired Bmsmentioning
confidence: 99%